Pengembangan Platform Komunitas Thrivian Berbasis Web Untuk Media Kolaborasi Digital - Samsu Hidayattullah, Muhammad; Izman Herdiansyah , Muhammad (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2024)
Online communities are essential for fostering interaction, collaboration, and the growth of individuals with shared interests. Yet, many current platforms lack a well-structured framework and robust collaborative features. This paper explores the creation of the Thrivian website, a digital platform tailored to facilitate collaboration, idea sharing, and networking. Thrivian integrates features like discussion forums, document sharing tools, and learning resources, empowering members in both personal and professional development. Its intuitive interface enhances accessibility, promotes member engagement, and streamlines community management. The platform aspires to establish an inclusive environment that nurtures collaboration, drives collective progress, and strengthens connections within the community. Thrivian aims to address challenges faced by online communities, boost productivity, and enable its members to achieve shared objectives effectively